Valoración técnico táctico en los entrenamientos de fútbol de la categoría juvenil en la academia Cristian Mora en el período agosto– enero 2023 - Chávez Mora, Dionicio German (2023)
he present research had as objective: To establish the tactical technical assessment in the football training of the youth category at the Cristian Mora Academy, in this sense a methodology of practical work of descriptive, correlational type was used selecting 22 players of the youth category comprised in ages between 16 to 18 years to which a questionnaire of technique and tactics was applied both individually and collectively, the data obtained was carried out an exhaustive and thorough evaluation and analysis allowing to evidence certain deficiencies in the players in terms of technique and facts in football, the proposal raised was validated by experts in the world of professional football as is the case of the World Cup goalkeeper Mr. Cristian Mora, the results obtained were of great help to the coach at the time of applying this manual being able to show by the entire coaching staff a significant improvement relevant point for the benefit of all the players of the youth category as well as for the managers of the academy, coming to the conclusion that the technical and tactical assessment in youth football is essential for the development of the players, this by focusing on individual skills, decision making, adaptability, competence, teamwork and continuous evaluation, which helps the manager to be in a better position to maximize the potential of his players and build a successful team